Kepuasan Siswa terhadap Kinerja Guru BK dalam Pelayanan Konseling Individual - Jaeti, Nur Fadillah; Ahmad, Mujahida (Universitas Ahmad Dahlan, 2016)
This study aimed to discover the studentsâ satisfaction towards the counselorâ performance in the individual counseling service on SMP Muhammadiyah 6 Yogyakarta. This was a descriptive quantitative study. The data of this study were collected through questionnaires. The subjects of this study were thirty-five students. This study employed descriptive statistical analysis to analyze the data. The result of this study showed that the studentsâ satisfaction towards the school counselor performance covers three aspects of individual counseling service (the beginning, the middle, and the end) in SMP Muhammadiyah 6 Yogyakarta. Six students were categorized as very satisfied (17%), twenty three students were categorized as satisfied (66%), and six students were categorized as not satisfied (17%).Â The result of this study can be a reference for school counselor as the evaluation in improving the quality of school counselorâ performance in the individual counseling service.